An overview of pervasive computing - Gupta, S.K.S.; Wang-Chien Lee; Purakayastha, A.; Srimani, P.K. (IEEE personal communications, 2001)
The importance of pervasive computing is rapidly increasing with the current trend toward universal presence of mobile computing, computer networks, and wireless communications in everyday life. In the last decade, there has been a dramatic increase in the use of companion devices and embedded computing devices. For example, wirelessly connected organizers and smartphones are becoming popular, and digital computing in some form is now an integral part of numerous everyday appliances. This has led to a change in the way we perceive computing and computers. Computers are no longer standalone special-purpose machines to be used by experts; rather, they are ubiquitously present in a networked environment to serve myriad needs of everyday life. The change in our perception of computing and computing devices, and their ever increasing presence in our everyday life is the subject of the new field known as pervasive computing.